Cutaneus Stimulation: Slow-Stroke Back Massage Reduces the Intensity of Osteoartritis Pain of Elderly - Mira Triharini; Mardliyah Mardliyah; Setho Hadisuyatmana (Universitas Airlangga, 2010)
Introduction: Osteoarthritis disease is the result of both mechanical and biological process which lead come to unstable degradation and synthesis of condrozyte cartilage and extracellular matrix. The risk factor of this instability is aging process. The aging process stimulates osteophytes formation and degradation of cartilage, and emerged pain as primary clinical symptom. One of the non pharmacological ways to cope this pain is by applying cutaneus stimulation through slow-stroke back massage method. The objective of this study was to analyze the effect of applying cutaneus stimulation with slow-stroke back massage method to osteoarthritis’s pain intensity.Methods: Pre experimental design with one group pre test-post test approach was used in this study. The subject of this study were elderly above 50 years old living in Panti Werdha Hargo Dedali Surabaya, 15 participants were involved using purpose sampling technique. This study started on January 29th until February 6th, 2010. Data were collected by interview and observation and analyzed by WIlcoxcon Signed Rank Test α = 0.05, p value <α.Results: The Result showed that the message intervention was significantly affect the elder’s level of osteoarthritis pain in Panti Werdha Hargo Dedali Surabaya (p = 0.003).Conclusion: It can be concluded that gives stimulation cutaneus: slow-stroke back massage reduce osteoathritis pain intensity. Slow-stroke back massage increase level of endorphin, so that pain reduction and individual pain perception will decrease.